The Role of Islamic Education in Shaping Social Media Ethics Among the Younger Generation - Nadia Sandi Rahmah; Rosdialena R (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The rapid development of digital technology has transformed communication patterns and social interactions, making social media an inseparable part of young people's daily lives. Alongside its benefits, social media also presents various ethical challenges, including the spread of misinformation, cyberbullying, hate speech, and irresponsible online behavior. These conditions highlight the need for moral and ethical guidance that can direct young people toward responsible digital engagement. This study aims to analyze the role of Islamic education in shaping social media ethics among the younger generation and to identify Islamic values that can serve as guidelines for behavior in digital spaces. The research employed a qualitative approach using a library research method. Data were collected from primary sources, including the Qur'an, Hadith, and major works on Islamic education, as well as secondary sources such as scientific journals, books, and previous studies related to digital ethics and social media. The findings indicate that Islamic education contributes significantly to the development of ethical digital behavior through the internalization of moral values, particularly tabayyun (verification of information), respectful communication, amanah (trustworthiness), and moral responsibility. These values encourage critical thinking, responsible information sharing, and constructive online interaction. The study concludes that strengthening digital literacy alone is insufficient to address ethical issues in social media use; rather, integrating Islamic educational values is essential for fostering a generation that is technologically competent, morally aware, and socially responsible in the digital era